2018
DOI: 10.3390/su10062051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Nitrogen Oxides and Ultrafine Particulate Matter Emission Features of Urban Bus Based on Real-World Driving Conditions in the Yangtze River Delta Area, China

Abstract: A Portable Emission Measurement System was used in this study to evaluate the exhaust emission characteristics of nitrogen oxides (NOx), ultrafine particulate matter (PM), and ultrafine particulate number (PN) from buses in the Yangtze River Delta, China. Results showed that NOx emission factor (unit: g•km −1) increased from 5.0 to 19.1, and PM emission factor (unit: g•km −1) increased from 0.001 to 0.189. A nonlinear model was established based on scientific statistical method, which showed that NOx and PM em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…It was shown that compared to older technologies there is a huge improvement; nevertheless, the ultimate goal is to reach almost zero emission levels. The same applies to other diesel heavy-duty trucks which usually have high emissions under city conditions [14,21,35]. One approach is using compressed natural gas (CNG) vehicles that had lower NO x emissions than diesel vehicles [9,10,13,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that compared to older technologies there is a huge improvement; nevertheless, the ultimate goal is to reach almost zero emission levels. The same applies to other diesel heavy-duty trucks which usually have high emissions under city conditions [14,21,35]. One approach is using compressed natural gas (CNG) vehicles that had lower NO x emissions than diesel vehicles [9,10,13,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether this is still true compared to the Euro VI diesel vehicles has to be investigated [14]. Other concepts such as hybridization need to be evaluated in the future, as in some cases they show reductions [13,35], but concerns regarding the operating temperature of the after-treatment devices were also raised [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As confirmed in the previous study of IEA (International Energy Agency), 23% of the total carbon dioxide emissions in the world was contributed by the transportation sector, including automobiles, light trucks, freight trucks, and buses [8]. A heavy duty vehicle such as bus can emit nitrogen oxides and PM0.1 (particulate matter with a diameter less than 0.1 μm) with the emission factors up to 5 g/ km for nitrogen oxides and 0.001 g/ km for PM0.1 [9]. A recent study also shows that vehicular traffic becomes a contributor to air pollution.…”
Section: Introductionmentioning
confidence: 99%
“…The second category aims to develop models to provide more precise knowledge about vehicle emissions in easily identifiable environments, which are called "micro" or "local" scale models. This approach offers the chance to acquire vehicle emissions data in real-world conditions [28,29]. Zhang et al investigated the emission characteristics of transportation vehicles using real data [30].…”
mentioning
confidence: 99%